The Optimum Level of Roselle (Hibiscus sabdariffa Linn.) - Kaewhom, Paitoon; Chauynarong, Navaporn (Journal of Mahanakorn Veterinary Medicine, 2018)
An experiment was conducted to examine the benefits of using roselle (Hibiscus sabdariffa Linn) dried calyx at varying levels (0, 2, 4 and 6%) in diets for laying hens at 18 weeks. Five hundred and seventy six 18-week old Hisex Brown pullets were randomly allotted into 4 groups of 6 replications, each replication containing 24 birds. Feed intake from 18 to 26 weeks of age was unaffected by the roselle supplement. From 19 to 23 weeks of age the highest egg production was observed in 6% roselle group. Inclusion of roselle at 6 % in the diet was found to increase (P<0.05) egg production at 21 and 22 weeks of age. However, at 24 weeks birds have the physiological stress, thus the lowest egg production was found in 6% roselle. By 26 weeks of age the egg production from birds in this group recovered and was higher than in other groups but this was not significantly different. Egg quality at 5 and 50% lay was not significantly different between the levels of roselle in diet (P>0.05). In conclusion, supplementation of 6% roselle calyx in chicken diets can improve egg production but it does not affect on egg quality.